Credit market competition and capital regulation - Franklin Allen; Elena Carletti; Robert Marquez (Goethe University Frankfurt, Center for Financial Studies (CFS), 2005)
Market discipline for financial institutions can be imposed not only from the liability side, as has often been stressed in the literature on the use of subordinated debt, but also from the asset side. This will be particularly true if good lending opportunities are in short supply, so that banks have to compete for projects. In such a setting, borrowers may demand that banks commit to monitoring by requiring that they use some of their own capital in lending, thus creating an asset market-based incentive for banks to hold capital. Borrowers can also provide banks with incentives to monitor by allowing them to reap some of the benefits from the loans, which accrue only if the loans are in fact paid o.. Since borrowers do not fully internalize the cost of raising capital to the banks, the level of capital demanded by market participants may be above the one chosen by a regulator, even when capital is a relatively costly source of funds. This implies that capital requirements may not be binding, as recent evidence seems to indicate.
urn:nbn:de:hebis:30-18130
Keywords: G21; G38; 330; Banking; Costly Capital; Asset Side Market Discipline; Kreditmarkt; Wettbewerb; Moral Hazard; Eigenkapitalvorschriften; Einlagensicherung; Theorie